Identification of a novel RPGR mutation associated with retinitis pigmentosa and primary ciliary dyskinesia in a Slovak family: a case report - Kolkova, Zuzana; Durdik, Peter; Holubekova, Veronika; Durdikova, Anna; Jesenak, Milos; Banovcin, Peter (Frontiers in Pediatrics, 2024)
Background The mutations in the RPGR (retinitis pigmentosa GTPase regulator) gene are the most common cause of X-linked retinitis pigmentosa (XLRP), a rare genetic disorder affecting the photoreceptor cells in the retina. Several reported cases identified this gene as a genetic link between retinitis pigmentosa (RP) and primary ciliary dyskinesia (PCD), characterised by impaired ciliary function predominantly in the respiratory tract. Since different mutations in the same gene can result in various clinical manifestations, it is important to describe a correlation between the gene variant and the observed phenotype. Methods Two young brothers from a non-consanguineous Slovak family with diagnosed retinal dystrophy and recurrent respiratory infections were examined. Suspected PCD was diagnosed based on a PICADAR questionnaire, nasal nitric oxide analysis, transmission electron microscopy, high-speed video microscopy analysis, and genetic testing. Results We identified a novel frameshift RPGR mutation NM_001034853: c.309_310insA, p.Glu104Argfs*12, resulting in a complex X-linked phenotype combining PCD and RP. In our patients, this mutation was associated with normal ultrastructure of respiratory cilia, reduced ciliary epithelium, more aciliary respiratory epithelium, shorter cilia, and uncoordinated beating with a frequency at a lower limit of normal beating, explaining the clinical manifestation of PCD in our patients. Conclusion The identified novel pathogenic mutation in the RPGR gene expands the spectrum of genetic variants associated with the X-linked PCD phenotype overlapping with RP, highlighting the diversity of mutations contributing to the disorder. The described genotype–phenotype correlation can be useful in clinical practice to recognise a broader spectrum of PCD phenotypes as well as for future research focused on the genetic basis of PCD, gene interactions, the pathways implicated in PCD pathogenesis, and the role of RPGR protein for the proper functioning of cilia in various tissues throughout the body.